Answer:
I believe there are only 5...
Answer:
If we put x=2 in the given equation, we get the answer for the equation as 2
Given:
![\sqrt{-3 x+10}=x](https://tex.z-dn.net/?f=%5Csqrt%7B-3%20x%2B10%7D%3Dx)
To find:
Why the answer is 2
Solution:
If we substitute the value x=2 in the given option, we get
![\sqrt{-3(2)+10}=2](https://tex.z-dn.net/?f=%5Csqrt%7B-3%282%29%2B10%7D%3D2)
![\sqrt{-6+10}=2](https://tex.z-dn.net/?f=%5Csqrt%7B-6%2B10%7D%3D2)
![\sqrt{4}=2](https://tex.z-dn.net/?f=%5Csqrt%7B4%7D%3D2)
Result:
Thus we can say that when substitute the value of x=2
We get the answer as ![\sqrt{-3 x+10}=2](https://tex.z-dn.net/?f=%5Csqrt%7B-3%20x%2B10%7D%3D2)
Answer:
![x^4 + 4x^3 + 6x^2 + 7x + 2](https://tex.z-dn.net/?f=x%5E4%20%2B%204x%5E3%20%2B%206x%5E2%20%2B%207x%20%2B%202)
Step-by-step explanation:
We are asked to multiply the given polynomials.
![(x^ 2 + 3x + 1) \times (x^2 + x + 2)](https://tex.z-dn.net/?f=%28x%5E%202%20%2B%203x%20%2B%201%29%20%5Ctimes%20%28x%5E2%20%2B%20x%20%2B%202%29)
Multiply each term of the first polynomial to each term of the second polynomial.
![x^ 2 \times (x^2 + x + 2) = x^4 + x^3 + 2x^2](https://tex.z-dn.net/?f=x%5E%202%20%20%5Ctimes%20%28x%5E2%20%2B%20x%20%2B%202%29%20%3D%20x%5E4%20%2B%20x%5E3%20%2B%202x%5E2)
![3x \times (x^2 + x + 2) = 3x^3 + 3x^2 + 6x](https://tex.z-dn.net/?f=3x%20%20%5Ctimes%20%28x%5E2%20%2B%20x%20%2B%202%29%20%3D%203x%5E3%20%2B%203x%5E2%20%2B%206x)
![1 \times (x^2 + x + 2) = x^2 + x + 2](https://tex.z-dn.net/?f=1%20%5Ctimes%20%28x%5E2%20%2B%20x%20%2B%202%29%20%3D%20%20x%5E2%20%2B%20x%20%2B%202)
Add the results
![(x^4 + x^3 + 2x^2) + (3x^3 + 3x^2 + 6x) + ( x^2 + x + 2)](https://tex.z-dn.net/?f=%28x%5E4%20%2B%20x%5E3%20%2B%202x%5E2%29%20%2B%20%283x%5E3%20%2B%203x%5E2%20%2B%206x%29%20%2B%20%28%20x%5E2%20%2B%20x%20%2B%202%29)
Combine the like terms
![x^4 + 4x^3 + 6x^2 + 7x + 2](https://tex.z-dn.net/?f=x%5E4%20%2B%204x%5E3%20%2B%206x%5E2%20%2B%207x%20%2B%202)
The answer is written in descending powers of x.
Answer:
x = 9.6
Step-by-step explanation:
Before we can figure out what x is, we need to figure out what the unlabeled side is. To figure that out, multiply the hypotenuse (12) by the sine of the angle labeled (34)
12 * sin(34)
<em>sin(34) equals 0.559192903470747; I'll round it to 0.6 for convenience.</em>
12 * 0.6
<em>Now simply multiply 12 by 0.6 to get 7.2.</em>
The unlabeled side is approx. 7.2 units long.
Now we know what the unlabeled side is. Now, to find x, find the square root of 12 squared minus 7.2 squared.
x = √12² - 7.2²
<em>12 squared is 144; 7.2 squared is 51.84.</em>
x = √144 - 51.84
<em>Subtract 51.84 from 144 to get 92.16.</em>
x = √92.16
<em>The square root of 92.16 is 9.6 (on the spot!).</em>
x equals 9.6.
Answer:
40%
Step-by-step explanation:
40-24=16
16/40 ×100 =40%